Experimental Study of the Basic Mechanical Properties of Directionally Distributed Steel Fibre-Reinforced Concrete - Fang-Yuan Li; Cheng-Yuan Cao; Yun-Xuan Cui; Pei-Feng Wu (Advances in Materials Science and Engineering)
Directionally distributed steel fibre-reinforced concrete (SFRC) cannot be widely applied due to the limitations of current construction technology, which hinders research on its mechanical properties. With the development of new construction technologies, such as self-compacting concrete or 3D printing, directionally distributed SFRC has found new developmental opportunities. This study tested, compared, and analysed the basic mechanical properties of ordinary concrete, randomly distributed SFRC, and directionally distributed SFRC. The differences between the damage patterns parallel and perpendicular to the direction of the steel fibres were evaluated in directionally distributed SFRC. When the fibre volume fraction is high and the compression is applied perpendicular to the fibre direction, as the loading increases, the transverse deformation of the specimen is constrained by the fibres. When the compression is applied parallel to the fibre direction, the fibre cannot effectively constrain the transverse deformation of the specimens. When the volume fraction of directionally distributed steel fibres was 1.6%, the elastic modulus of the directionally distributed steel fibres was 39% higher than that of ordinary concrete. Comparison of the experimental values of the elastic modulus with those estimated by existing calculation methods revealed that a modification of the current calculation theories may be required to calculate the changes in the elastic modulus of directionally distributed SFRC with a high volume fraction of steel fibres.